Waardenburg Syndrome Type 1 Coexisting with Unilateral Glaucoma: A Case Report - Pierre, Lucas Linhares; Cisne, Ana Camille Feijão; Pierre, Lara Linhares; Pierre-Filho, Paulo de Tarso Ponte (Brazilian Journal of Case Reports, 2026)
Waardenburg syndrome (WS) is a rare disorder of neural crest cell development classified into four main clinical and genetic phenotypes. The range and severity of associated symptoms and findings may vary greatly from case to case. There are few reports of WS associated with ocular disorders. Here, we describe a case of WS type1 combined with open-angle glaucoma and emphasize the importance of observation of comorbidities that can coexist with the syndrome. Early diagnosis and intervention can lead to better outcomes.